2000
DOI: 10.1046/j.1432-1327.2000.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

The gene encoding polyneuridine aldehyde esterase of monoterpenoid indole alkaloid biosynthesis in plants is an ortholog of theα/β hydrolase super family

Abstract: The biosynthesis of the anti‐arrhythmic alkaloid ajmaline is catalysed by more than 10 specific enzymes. In this multistep process polyneuridine aldehyde esterase (PNAE) catalyses a central reaction by transforming polyneuridine aldehyde into epi‐vellosimine, which is the immediate precursor for the synthesis of the ajmalane skeleton. PNAE was purified from cell suspension cultures of Rauvolfia serpentina. The N‐terminal sequence and endoproteinase LysC fragments of the purified protein were used for primer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 34 publications
0
96
0
5
Order By: Relevance
“…Site-directed mutagenesis of (His) 6 PNAE was achieved using the QuikChange TM in vitro Site-Directed Mutagenesis Kit, according to the manufacturer's recommendations. For generation of the mutant enzymes, the following oligonucleotides were used: C20A: 5¢-CTGGTACACGGCGGAT GTCTCGGAGCTTGGATCTGG-3¢.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Site-directed mutagenesis of (His) 6 PNAE was achieved using the QuikChange TM in vitro Site-Directed Mutagenesis Kit, according to the manufacturer's recommendations. For generation of the mutant enzymes, the following oligonucleotides were used: C20A: 5¢-CTGGTACACGGCGGAT GTCTCGGAGCTTGGATCTGG-3¢.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…After centrifugation (10 000 g, 20 min) total PNAE activity was determined in the supernatant. (His) 6 PNAE wild-type protein and the muteins were purified on self packed Ni 2+ resin columns (0.7 cm internal diameter · 1 cm). For the washing steps, the above mentioned buffer containing 20 and 50 mM imidazole, each of 20 mL was used and elution was performed with 250 mM imidazole.…”
Section: Enzyme Expression and Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…All biosynthetic transformations leading from strictosidine to ajmaline have been detected in enzyme fractions from Rauwolfia cell culture, though only six biosynthetic genes have been cloned and characterized (Figure 1). 4, 5, 6, 7, 8, 9, 10, 11 Several studies showed that vomilenine is an ajmaline biosynthetic intermediate that is produced through selective hydroxylation of vinorine at the C‐21 position by Rauwolfia cell culture extracts (Figure 1). 12, 13, 14 However, no enzyme isolated from R. serpentina has shown this activity 11…”
mentioning
confidence: 99%